2016
DOI: 10.2147/ott.s106926
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of expression of the nuclear receptor NR0B2 (small heterodimer partner 1) and its impact on proliferation of renal carcinoma cells

Abstract: Mammalian nuclear receptors (NRs) are transcription factors regulating the expression of target genes that play an important role in drug metabolism, transport, and cellular signaling pathways. The orphan and structurally unique receptor small heterodimer partner 1 (syn NR0B2) is not only known for its modulation of drug response, but has also been reported to be involved in hepatocellular carcinogenesis. Indeed, previous studies show that NR0B2 is downregulated in human hepatocellular carcinoma, suggesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Our data confirmed the predominant expression profile of the NR0B2 gene in benign liver and kidney tissues. Interestingly, NR0B2 expression was significantly downregulated in malignant tissues derived from these organs, consistent with previous reports (10,14,43), indicating a dramatic alteration in regulating NR0B2 gene expression after malignant transformation. Higher NR0B2 expression is associated with fewer disease relapse and progression in liver cancer patients and is also associated with a favorite overall survival prognosis in human breast cancers, lung adenocarcinomas, liposarcomas, and eye uveal melanomas.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our data confirmed the predominant expression profile of the NR0B2 gene in benign liver and kidney tissues. Interestingly, NR0B2 expression was significantly downregulated in malignant tissues derived from these organs, consistent with previous reports (10,14,43), indicating a dramatic alteration in regulating NR0B2 gene expression after malignant transformation. Higher NR0B2 expression is associated with fewer disease relapse and progression in liver cancer patients and is also associated with a favorite overall survival prognosis in human breast cancers, lung adenocarcinomas, liposarcomas, and eye uveal melanomas.…”
Section: Discussionsupporting
confidence: 91%
“…There is a paucity of NR0B2 expression from human cancer specimens, and so far, only two reports showed NR0B2 downregulation in 10 cases of liver cancers (HCC) ( 14) and 24 cases of renal cancers (RCC) (10). With the advance of bioinformatic technologies, many public databases are assessable to analyze gene expression profiles in a variety of human cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely expressed in many organs that play an essential role in development, cellular homeostasis, and disease including cancer where over‐ or under‐expression of some receptors has prognostic significance for cancer patient survival as reviewed 27,42 . Recent studies have implicated NR0B2 ' s tumor suppressor role in renal carcinoma, breast, prostate and also liver cancer, summarized in Supplementary Table S3 20,42‐48 . In elaboration, He et al 45 reported extensive methylation of NR0B2 and downregulation of NR0B2 mRNA expression in human hepatocellular carcinoma (HCC) tissues compared to adjacent healthy tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al 49 showed that overexpression of NR0B2 in HCC cells inhibits invasion and migration, and expression of NR0B2 is negatively associated with cancer metastasis in human HCC and gastric cancer. Prestin et al 43 reported downregulation of NR0B2 in human renal cell carcinoma compared to adjacent healthy tissues. Nevertheless, the underlying mechanisms that trigger altered expression of NR0B2 in specific tumors has not been reported, and there are currently no germline NR0B2 variants known to be associated with cancer.…”
Section: Discussionmentioning
confidence: 99%